Upaya Penguatan Kapabilitas Masyarakat dalam Pengenalan Perilaku Hidup Bersih dan Sehat (PHBS) di Era New Normal - Sucipto Sucipto; Siti Istiqomah (UIN Raden Mas Said Surakarta, 2020)
The lack of socialization of Covid-19 in remote villages has caused the public to pay less attention to the Coronavirus. Through community service and research activities conducted by students using direct observation methods in the community, interviews and documentation and tracing and analyzing problems faced by the village, especially the problem of implementing health protocols in the new normal era. Therefore, the service that was carried out at Dukuh Sulicilik, Jebugan Village, North Klaten led to education about Covid-19, the implementation of health protocols in the New Normal era, as well as the introduction of the community to the culture of Clean and Healthy Living Behavior (PHBS) to create a more life. healthy, clean and high quality.